FROM RECRUITMENT TO REDUNDANCY: A SYSTEMATIC LITERATURE REVIEW OF THE IMPACT OF ARTIFICIAL INTELLIGENCE ON HR MANAGEMENT PRACTICES, ALGORITHMIC BIAS, AND THE URGENCY OF LABOUR REGULATION IN INDONESIA - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study presents a systematic literature review on the use of artificial intelligence (AI) in human resource management (HRM) practices, ranging from recruitment to redundancy, with a focus on algorithmic bias and the urgency of labour regulation in Indonesia. Through a thematic analysis of various literature, this article identifies how AI is transforming recruitment procedures, selection, development, performance appraisal, and decision-making regarding termination of employment, whilst highlighting the potential for efficiency and improved organisational performance, which is offset by risks of discrimination, lack of transparency, and dehumanisation in employment relationships. The study also emphasises that labour regulations in Indonesia have yet to accommodate the characteristics of AI; consequently, an adaptive, worker-friendly legal framework is required, grounded in the principles of justice, non-discrimination, transparency, and algorithmic accountability.